Whole-body cortisol increases after direct and visual contact with a predator in zebrafish, Danio rerio - Barcellos, Leonardo Jose Gil; Ritter, Filipe; Kreutz, Luiz Carlos; Quevedo, Rosmari Mezzalira; da Silva, Leonardo Bolognesi; Bedin, Alexandra Calliari; Finco, Jovani; Cericato, Leonardo (Elsevier B.V., 2007)
Ornamental fish may be severely affected by a stressful environment. Stressors impair the immune response, reproduction and growth rate; thus, the identification of possible stressors will aid to improve the overall quality of ornamental fish. The aim of this study was to determine whole-body cortisol of adult zebrafish, Danio rerio, following visual or direct contact with a predator species. Zebrafish were distributed in three groups: the first group, which consisted of zebrafish reared completely isolated of the predator, was considered the negative control; the second group, in which the predator, Parachromis managuensis was stocked together with zebrafish, was considered the positive control; the third group consisted of zebrafish stocked in a glass aquarium, with direct visual contact with the predator. The mean whole-body cortisol concentration in zebrafish from the negative control was 6.78 +/- 1.12 ng g(-1), a concentration statistically lower than that found in zebrafish having visual contact with the predator (9.26 +/- 0.88 ng g(-1)) which, in turn, was statistically lower than the mean whole-body cortisol of the positive control group (12.35 +/- 1.59 ng g(-1)). The higher whole-body cortisol concentration found in fish from the positive control can be attributed to the detection, by the zebrafish, of relevant risk situations that may involve a combination of chemical, olfactory and visual cues. One of the functions of elevated cortisol is to mobilize energy from body resources to cope with stress. The elevation of whole-body cortisol in fish subjected to visual contact with the predator involves only the visual cue in the recognition of predation risk. We hypothesized that the zebrafish could recognize predator characteristics in P managuensis, such as length, shape, color and behavior. Nonetheless, the elevation of whole-body cortisol in zebrafish suggested that the visual contact of the predator may elicit a stress response in prey fish. This assertion has a strong practical application concerning the species distribution in ornamental fish markets in which prey species should not be allowed to see predator species. Minimizing visual contact between prey and predator fish may improve the quality, viability and welfare of small fish in ornamental fish markets. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: zebrafish; ornamental fish business; predator; stress; whole-body cortisol